Trading and Pricing in Upstairs and Downstairs Stock Markets - Booth, G. Geoffrey; Lin, Ji-Chai; Martikainen, Teppo; Tse, Yiuman (Review of Financial Studies, 2002)
We provide empirical evidence on the economic benefits of negotiating trades in the upstairs trading room of brokerage firms relative to the downstairs market. Using Helsinki Stock Exchange data, we find that upstairs trades tend to have lower information content and lower price impacts than downstairs trades. This is consistent with the hypotheses that the upstairs market is better at pricing uninformed liquidity trades and that upstairs brokers can give better prices to their customers if they know the unexpressed demands of other customers. We find that these economic benefits depend on price discovery occurring in the downstairs market.